"Hands up, don't shoot" or shut up and play ball? Fan-generated media views of the Ferguson Five. Issue 3 (18th May 2016) - Gill, Emmett L.
ABSTRACT: This article explores the intersection of sports and social activism in the wake of the police-involved death of Michael Brown. Traditionally, professional athletes have remained silent, or at the very best color-blind, regarding domestic social issues. It is customary for sports celebrities such as Michael Jordan to avoid compromising their status in the marketplace with politics, even when the social matter impacts males who look like them and unswervingly support their craft. Yet, in the wake of the death of Brown, several professional athletes, if only briefly, engaged in their own forms of activism. This article will implore a qualitative content analysis of mainstream media accounts and user-generated content to develop a case study on how Black professional athletes responded to police-involved deaths of Black men. In particular, the author will use the "data" to develop a case study on five St. Louis Rams athletes who staged a silent, pregame protest in the wake of the civil unrest in Ferguson, Missouri. The case study will include the response from the St. Louis police department and the National Football League. Fan-generated media content about the "Ferguson Five" will be used to analyze public perceptions of athlete activism. A grounded theory approach will be used to examine the immediate and intermediate prospect of civic involvement of professional athletes in social issues.